2018
DOI: 10.1016/j.nmni.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Shewanella algae infection in Italy: report of 3 years' evaluation along the coast of the northern Adriatic Sea

Abstract: Shewanella algae are Gram-negative, nonfermentative, motile bacilli, classified in the genus Shewanella in 1985. These environmental bacteria are occasionally identified in human infections, with a relatively strong association with exposure to seawater during warm seasons. This report describes a case series of 17 patients with infection correlated to S. algae in the coastal area of Romagna, Italy, from 2013 to 2016. The types of infection included otitis, pneumonia, sepsis and soft tissue (wound). Exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…This is probably due to the fact that they are still unknown and not reported on databases. Considering the data reported in literature, very high MICs were observed by Torri and coworkers [73] in clinical S. algae isolates during an Italian survey on shewanella-associated infections. This is probably an intrinsic resistance present in S. algae strains whose gene may be chromosomal-encoded considering a few presence of plasmids in these strains.…”
Section: Discussionmentioning
confidence: 87%
“…This is probably due to the fact that they are still unknown and not reported on databases. Considering the data reported in literature, very high MICs were observed by Torri and coworkers [73] in clinical S. algae isolates during an Italian survey on shewanella-associated infections. This is probably an intrinsic resistance present in S. algae strains whose gene may be chromosomal-encoded considering a few presence of plasmids in these strains.…”
Section: Discussionmentioning
confidence: 87%
“…Many labs in the past were not able to distinguish Shewanella putrefaciens and algae. Over the past decade, the use of matrix-assisted laser desorption/ionization time-of-flight mass spectrometry has enabled detection of the latter and thus we see an increasing number of infections caused by Shewanella algae [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Torri et al. in 2017 published a case series of 17 patients with Shewanella infection in Italy [18]. Among these patients, five (29.4%) had a SSTI and another five (29.4%) had sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, to support the significance of seawater exposure in the pathogenesis of the Shewanella infection, Tori et al reported that two patients in the sepsis group and four patients in the SSTI group, respectively, had contact with seawater within previous four weeks. The only patient who died had Shewanella positive blood cultures and sepsis [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation